2018
DOI: 10.1021/acs.langmuir.8b00420
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Like Assembly of Silica Nanospheres in the Presence of Amphiphilic Block Copolymer: Effects of Particle Size

Abstract: Block copolymer-mediated self-assembly of colloidal nanoparticles has attracted great attention for the fabrication of a wide variety of nanoparticle arrays. We have previously shown that silica nanospheres (SNSs) 15 nm in diameter assemble into ring-like nanostructures in the presence of amphiphilic block copolymers poly[(2-ethoxyethyl vinyl ether)- block-(2-methoxyethyl vinyl ether)] (EOVE-MOVE) in an aqueous phase. Here, the effects of particle size of SNSs on this polymer-mediated self-assembly are studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 56 publications
1
15
1
Order By: Relevance
“…In this approach, the arrangement of nanoparticles in the polymer matrix is controlled by the self-assembly of block copolymers, which forms a range of different nanostructures such as spheres, cylinders, gyroids, and lamella through the microphase segregation of two polymer blocks . Thermodynamic considerations indicate that nanoparticles can be incorporated into one of the two polymer domains or at the interface between polymer blocks, depending on the surface nature and size of the nanoparticles. , Often in cases, the incorporation of nanoparticles affects the self-assembly behavior of the block copolymers, resulting in unexpected and in some cases unusual assembly structures. Such behavior has been actively studied for thin film and solution phase self-assembly. For example, Kramer and co-workers reported that the incorporation of polystyrene-coated gold nanoparticles in a thin film self-assembly of polystyrene- block -poly­(2-vinylpyridine) caused a morphological transition from lamella to sphere by the swelling of a selective domain .…”
mentioning
confidence: 99%
“…In this approach, the arrangement of nanoparticles in the polymer matrix is controlled by the self-assembly of block copolymers, which forms a range of different nanostructures such as spheres, cylinders, gyroids, and lamella through the microphase segregation of two polymer blocks . Thermodynamic considerations indicate that nanoparticles can be incorporated into one of the two polymer domains or at the interface between polymer blocks, depending on the surface nature and size of the nanoparticles. , Often in cases, the incorporation of nanoparticles affects the self-assembly behavior of the block copolymers, resulting in unexpected and in some cases unusual assembly structures. Such behavior has been actively studied for thin film and solution phase self-assembly. For example, Kramer and co-workers reported that the incorporation of polystyrene-coated gold nanoparticles in a thin film self-assembly of polystyrene- block -poly­(2-vinylpyridine) caused a morphological transition from lamella to sphere by the swelling of a selective domain .…”
mentioning
confidence: 99%
“…The implications of the current work are not limited exclusively to the analysis of binary assemblies because the techniques developed for the identification and characterization of particle sub-assemblies are remarkable for an ample range of particle assemblies. Sparse assemblies characterized by the presence of chains, rings and small clusters have been encountered in very different contexts within the field of colloid science [31,33,34,35,37]. Such arrangements have been demonstrated to influence, for instance, the optical properties of colloidal assemblies [36].…”
Section: Discussionmentioning
confidence: 99%
“…Chaining has been observed in self-assembly based on the use of electric and magnetic fields [31,32,33]. More recently, ring-like assemblies have been examined within the framework of block copolymer-mediated self-assembly of nanoparticles [34]. Anisotropic assembly phases, in particular chains, have been found in the investigation of the interfacial behavior of colloidal particles in a Langmuir trough in the presence of surfactants, block copolymers and proteins [35,36]; chaining has been witnessed under specific experimental conditions in terms of the spreading agent, subphase pH and conditions of injection of a colloidal suspension to the air/water interface [37].…”
Section: Introductionmentioning
confidence: 99%
“…Among hollow silica nanoparticles, special attention has been given to the preparation of anisotropic, single-hole nanoparticles (i.e., nanocups) because they may find many applications such as carriers for nanomedicine materials, 21 templates for optical materials, 22 and as anisotropic building units for self-assembly. 23 Although there have been no bioinspired approaches, several methods for the fabrication of nanocups were reported. Lim et al prepared silica nanocapsules (ca.…”
Section: ■ Introductionmentioning
confidence: 99%